Relation of respiratory muscle strength, cachexia and survival in severe chronic heart failure. Issue 4 (21st June 2013) - Habedank, Dirk; Meyer, F. Joachim; Hetzer, Roland; Anker, Stefan D.; Ewert, Ralf
Abstract : Background: Respiratory muscle (RM) function predicts prognosis in non‐cachectic patients with chronic heart failure (CHF). We hypothesized that weakness of RM (maximum inspiratory mouth occlusion pressure, Pimax ) is a function of body mass index, and that outcome is more a function of BMI than of Pimax or ventilatory drive (P0.1). Subjects and methods: We enrolled 249 CHF patients (11.2 % female, median age 54.2 years) at the German Heart Institute Berlin. Patients were in NYHA classes I/II/III/IV by n  = 16/90/108/35. All patients underwent tests of pulmonary function, RM (Pimax, P0.1), cardiopulmonary exercise testing (peakVO2, VE/VCO2‐slope), and right heart catheterization. Results: Mean follow‐up time was 18 (1–36) months, 47 patients (18.9 %) died or underwent cardiac assist implantation. Pimax correlated weakly with BMI ( r  = 0.19), peakVO2 ( r  = 0.15), and FEV1 ( r  = 0.34, all p  < 0.02), and was lower in females compared to males (3.9 ± 1.7 vs. 6.6 ± 2.7 kPa; p  < 0.001). P0.1 correlated with pulmonary pressure (rho = 0.2; p  < 0.01) and peakVO2 (rho = −0.14; p  < 0.02). Neither Pimax [hazard ratio (HR) 0.98; confidence interval (CI) 0.88–1.08] nor P0.1 (HR 0.52; 0.06–4.6) predicted survival. Multivariate regression analysis revealed gender, BMI, and FEV1 as cofactors of Pimax, with only BMI (HR 0.87; CI 0.80–0.95) predicting survival independently. The lowest quintile in BMI had the worst outcome (log‐rank χ ² = 13.5, p  = 0.009). Summary: In CHF patients including cachexia and NYHA IV, Pimax does not predict survival. Pimax depends on gender, BMI, FEV1, and peakVO2, with only BMI and peakVO2 predicting survival. The impaired Pimax in CHF might be a result of catabolism and weight loss and is not a predictive factor in itself.